1992
DOI: 10.1177/014920639201800204
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Functional Structures: A Review and Integration of Matrix Organization and Project Management

Abstract: In this article, we review and summarize the literature on crossfunctional organization forms that has been published since 1976. We focus on the commonalities of the literatures that deal with matrix organization and project management. With a definition of cross-functional organization in hand, we review the literature for advantages and disadvantages of these organization forms, ending the section with a discussion of the great needfor empirical research to resolve numerous questions and paradoxes. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
0
7

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(192 citation statements)
references
References 49 publications
5
174
0
7
Order By: Relevance
“…In the CMS case study, application designers (AD) and leading project managers (PM L ) with engineering background solved the technical problems, whereas in the wind turbine case study, technical engineers (TE) and technical account managers (TAM) in charge of the project teams were responsible for such problems. These professionals were accustomed to an organizing matrix structure based on project operations (Ford and Randolph, 1992;Knight, 1976), as their knowledge was often loaned to internal and customer projects for specific time periods. The length of their presence varied, but they were associated with project planning and implementation and motivated by project-related success criteria such as time, budget, and project performance (see Atkinson, 1999).…”
Section: Typical Professional and Occupational Groups In Service-intementioning
confidence: 99%
“…In the CMS case study, application designers (AD) and leading project managers (PM L ) with engineering background solved the technical problems, whereas in the wind turbine case study, technical engineers (TE) and technical account managers (TAM) in charge of the project teams were responsible for such problems. These professionals were accustomed to an organizing matrix structure based on project operations (Ford and Randolph, 1992;Knight, 1976), as their knowledge was often loaned to internal and customer projects for specific time periods. The length of their presence varied, but they were associated with project planning and implementation and motivated by project-related success criteria such as time, budget, and project performance (see Atkinson, 1999).…”
Section: Typical Professional and Occupational Groups In Service-intementioning
confidence: 99%
“…For the reasons described above for geographic distribution and cross-functionality, there is no evidence to suggest a direct effect of having different supervisors on performance. But, when members do not have the same supervisor, they run the risk of encountering increased role ambiguity, conflict among managers, and insecurity through reduced autonomy (Burns, 1989;Davis & Lawrence, 1977;Ford & Randolph, 1992). For example, if a work group has a project milestone to meet, but the supervisor of one of the members also has a competing deadline on another project that needs the assistance of the member, then tension is sure to arise.…”
Section: Hypothesis 2: As Cross-functionality Increases Internal Knomentioning
confidence: 99%
“…Numerous studies have been conducted on the implementation of matrix management and the advantages and problems relating to this type of company structure [4,3]. Although many authors have suggested possible solutions to the problems concerning matrix management in a project environment, empirical data regarding the impact of matrix structures on project management are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Although many authors have suggested possible solutions to the problems concerning matrix management in a project environment, empirical data regarding the impact of matrix structures on project management are lacking. Ford and Randolph [4] suggested a number of paradoxes between the advantages and disadvantages of matrix structures. This essentially means that although this organisational structure has many advantages, the disadvantages seem to play off against the advantages, thus leading to 'paradoxes'.…”
Section: Introductionmentioning
confidence: 99%